2019
DOI: 10.1021/acsami.9b12579
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Phase Stability of Inorganic α-CsPbI3 by the Bication-Conjugated Organic Molecule for Efficient Perovskite Solar Cells

Abstract: Inorganic CsPbI3 perovskite has demonstrated promising potentials for photovoltaic applications, whereas the black perovskite polymorph (α phase) of CsPbI3 was easily prone to converting into yellow phase (δ phase) under ambient moist environment, which restrained its practical application and further studies severely. In this study, p-phenylenediammonium iodide (PPDI) was employed to posttreat CsPbI3 films for controlling the phase conversion, strengthening moisture resistance, and improving device performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 27 publications
0
49
0
1
Order By: Relevance
“…We propose a mechanism to understand this behavior, summarized in Scheme 1. It is well known that the surface vacancies would generate substantial dangling bonds absorbing moisture that accelerate the phase transition [36]. Since the surface vacancies in the QDs with and without UV treatment are not determined by difference in the chemical surrounding, as we have demonstrated by FTIR and since inside the glovebox photo-oxidation unlikely occurs, the rise of the observed improved stability is explained through another mechanism.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…We propose a mechanism to understand this behavior, summarized in Scheme 1. It is well known that the surface vacancies would generate substantial dangling bonds absorbing moisture that accelerate the phase transition [36]. Since the surface vacancies in the QDs with and without UV treatment are not determined by difference in the chemical surrounding, as we have demonstrated by FTIR and since inside the glovebox photo-oxidation unlikely occurs, the rise of the observed improved stability is explained through another mechanism.…”
Section: Resultsmentioning
confidence: 56%
“…The shape of the IPCE spectra is consistent with previous work, reporting direct planar solar cells architecture, where the onset at short wavelengths is related to light absorbance from the ITO glass and SnO 2 [18] and the one at the long wavelengths is at 680 nm, below the onset around 700 nm of solar cells employing bulk CsPbI 3 . This demonstrates the preservation of the quantum confinement for both non-treated and UV treated devices [4,15,36,37].…”
Section: Resultsmentioning
confidence: 74%
“…Ding et al found that the existence of PPD cations could avoid spontaneous octahedral tilting by forming ionic bonds between NH 3+ of PPD 2+ and I − of [PbI 6 ] 4− ( Figure a). [ 105 ] The p ‐phenylenediammonium iodide (PPDI)‐treated PSCs exhibited a champion PCE of 10.4% and retained 91% of its initial PCE after 504 h storage in a dark dry box. Wang et al chose the phenylethylamine cation (PEA + ) to posttreat the surface of CsPbI 3 perovskite and achieved a stabilized PCE of 13.5%.…”
Section: Additive Engineerings At Perovskite/htl Interfacesmentioning
confidence: 99%
“…Reproduced with permission. [ 105 ] Copyright 2019, American Chemical Society. b) Schematic illustration of organic cation surface termination using PEAI.…”
Section: Additive Engineerings At Perovskite/htl Interfacesmentioning
confidence: 99%
“…The CsPbI 3 perovskite thin films with PVP additive are highly stabilized, 75% of the initial PCE is retained after the encapsulated PSC is exposed to ambient air with 50% relative humidity (RH) for 500 h. Surface capping with the long‐chain ammonium cations shows a universal way to stabilize the CsPbI 3 as well as improve the PCE through defect passivation. [ 95,98 ]…”
Section: Fabrication and Stabilization Of Cspbi3mentioning
confidence: 99%